Construction of basic logic gates based on rapid detection of transferrin conformations. (July 2020) - Fu, Yao; Shi, Lei; Yang, Da-wei; Liu, Lu; Zhang, Xiu-feng
Abstract: A simple technique for constructing different protein logic gates (OR and INHIBIT) using Fe 3+ and/or Al 3+ to regulate changes in the conformation of transferrin. Logic gates are easy to control and also display real-time responses to inputs. This study provides new insights into the use of different conformations to design transferrin logic gates and provides a means to further detect transferrin in serum systems. Highlights: Construction of protein-based logic gates (OR and INHIBIT) using different transferrin conformations. Conformal changes of transferrin regulated by Fe 3+ and Al 3+ . Using ETC supramolecular aggregates as probes.